Pb(Zn1/3Nb2/3)O3–PbTiO3 single crystal and device development - L. C. Lim; S. Zhang; Y. X. Xia; D. H. Lin; N. H. L. Goh (Journal of Advanced Dielectrics, 2014)
This paper describes recent device developments with relaxor ferroelectric Pb(Zn1/3Nb2/3)O3–PbTiO3 (PZN–PT) single crystals carried out at Microfine Materials Technologies Pte. Ltd, Singapore. Promising [011]-poled transverse cuts of PZN–PT single crystals and the results on the effect of electric field and axial compressive stress on the rhombohedral-to-orthorhombic (R–O) phase transformation behavior of such cuts are presented and discussed. The single crystal devices described include a compact low-frequency broadband power-efficient underwater tonpilz projector, high sensitivity shear accelerometers and acoustic vector sensors (AVS). The unique characteristics offered by these PZN–PT single crystal devices are highlighted, which serve as examples of new-generation piezoelectric devices and systems for a wide range of demanding applications.